Implication of Changes in the Imaging Measurements after Mechanically Aligned Total Knee Arthroplasty. Issue 12 (2nd November 2022) - Cheng, Long; Ren, Peng; Zheng, Qingyuan; Ni, Ming; Geng, Lei; Wang, Yi‐Ming; Zhang, Guo‐Qiang
Abstract : Objective: Imaging measurements allow assessment of the mechanical alignment before and after total knee arthroplasty (TKA). The changes in radiographic parameters in each period of time within 1 year after TKA has been poorly understood. The purpose of this study was to examine the timing and causes of imaging changes in lower extremity force lines after total knee arthroplasty with mechanical alignment. Methods: A total of 93 mechanically‐aligned TKA were radiographically examined before, 3 days, 3 months, and 1 year after surgery. Radiographic parameters included hip‐knee angle (HKA), lateral distal femoral angle (LDFA), medial proximal tibial angle (MPTA), knee joint line orientation (KJLO), ankle joint line orientation (AJLO), the knee joint line relative to ankle joint line angle (KJLTA) and midpoints of the ankle distance (MAD). Paired t ‐test were used to analyze the changes of these imaging parameters, By establishing a simple tibial model, the time points of changes in the imaging parameters after TKA was determined, with an attempt to understand the post‐TKA changes in these imaging parameters. Results: Statistically significant differences were found between the preoperative data and the data measured 3 days after surgery in HKA, LDFA, MPTA, MAD, KJLTA, AJLO ( P  < 0.05) while KJLO exhibited no significant difference ( P  = 0.089). There existed significant differences between the data measured 3 days and the measurements taken 3 months after operation in HKA, MPTA, KJLTA, KJLO, AJLO ( P  < 0.05), whereas LDFA and MAD showed no significant difference ( P  > 0.05). Significant differences were revealed between the data measured 3 months and those collected 1 year after surgery in LDFA, MPTA, AJLO, KJLTA ( P  < 0.05) but HKA, KJLO, AJLO showed no significant differences ( P  > 0.05). The tibial model was made to look into the changes in postoperative imaging parameters. ΔMAD and postoperative AJLO were calculated to verify the model and hypothesis. Conclusions: Postoperative changes in radiographic parameters and tibial models showed that the lower extremities were in an unnatural state within 1 year after TKA. The changes in the lower extremities force line were the results of the gradual adaptation of the lower extremities to TKA and the lateral swing of the extremities (3°) after surgery. Imaging data 1 year after surgery should be taken into account in the explanation of post‐TKA changes in lower limb force lines. Abstract : The tibia is simplified as a two‐dimensional graph, The lower extremities were in an unnatural state within one year after TKA. The changes of the lower extremities force line were actually the common results of the gradual adaptation of the lower extremities to TKA and the lateral swing of the extremities 3° after surgery.